Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) Regulates Neurite Outgrowth Through the Activation of Akt/mTOR and Erk/mTOR Signaling Pathways - Wen, Wen; Wang, Yongchao; Li, Hui; Xu, Hong; Xu, Mei; Frank, Jacqueline A.; Ma, Murong; Luo, Jia (Frontiers in Molecular Neuroscience, 2020)
Neurite outgrowth is essential for brain development and the recovery of brain injury and neurodegenerative diseases. In this study, we examined the role of the neurotrophic factor MANF in regulating neurite outgrowth. We generated MANF knockout (KO) neuronal cells (N2a) using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 and demonstrated that MANF KO neuronal cells failed to grow neurites in response to RA stimulation. Using MANF siRNA, this finding was confirmed in human neuronal cells (SH-SY5Y). Nevertheless, MANF overexpression by adenovirus transduction or addition of MANF into culture media facilitated the growth of longer neurites in RA-treated neuronal cells. MANF deficiency resulted in inhibition of Akt, Erk, mTOR, and P70S6, and impaired protein synthesis. MANF overexpression on the other hand facilitated the growth of longer neurites by activating Akt, Erk, mTOR, and P70S6. Pharmacological blockade of Akt, Erk or mTOR eliminated the promoting effect of MANF on neurite outgrowth. These findings suggest that MANF positively regulated neurite outgrowth by activating Akt/mTOR and Erk/mTOR signaling pathways.